Evaluasi kualitas lingkungan sebagai dampak beroperasinya Jalan tol ruas tol Solo -Mantingan segmen Colomadu - Karanganyar - Masrida, Reni (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
The development of the surrounding environment with the operation of the toll road section provides benefits to the community including travel time to the destination closer and faster and at night enough to provide lighting for residents along the toll road section. The research method used is descriptive quantitative and accidental sampling for the impact on the community. Furthermore, an evaluation of the tendency (trend) of changes in environmental quality in a certain range of space and time is carried out. To conduct this evaluation, monitoring data from time to time (time series data) is absolutely necessary, because the assessment of changes in trends can only be done with data for different monitoring times. The results of the analysis will provide information on follow-up efforts to improve the environment.